Analysis of the new perspective of journalistic documentation in the Spanish media - Marcos Recio, Juan Carlos; Edo, Concha (Revista General de Información y Documentación, 2015)
In an attempt toimprove the proposalsof information,thespanish media, through documentation centers, adapt to new times. A tour ofthe latest advancesin informationand documentationallows readers tostand in front ofthe challengesand tasksto buildgood information.Thistext alsodiscusses the use ofthe documentationby thespanish journalists, as well as the operation oftheir documentation centers, which thedocumentary serviceenvironment and its influenceis valuedinformationina surveythrough thePress AssociationofMadrid.Another objectiveis to knowthe use ofother sources of informationand databasesthat journalistsneeded to developquality content.Finallyreportersindicatingthe value tothemof social networksTwitter, Facebook andLinkedInare asked.